The concept of freedom in Christian and Islamic theology - Ali, Ali (Al-Adab Journal, 2022)
One of the most important basic concepts associating with the human being is the concept of freedom. Especially in contemporary philosophy, famous trends in the twentieth century established their bases on this concept such as existentialism philosophy, beside to huge number of inquiries presented by the rest of the philosophical doctrines and personalities. Despite this concept has been clarified clearly at the present time, however, it did not reach what it is now without going through turns and visions adopted by many previous philosophical developments. Religious field is not excluded from that, as the religions represented by their sacred texts and the visions of their believers are not devoid of addressing the issue of freedom. Of course, in the Christian and Islamic religions, the concept of freedom was not absent, and this is what we will discuss in the course of this research which is titled by 'The concept of freedom in Christian and Islamic theology'.